The gender gap in education investment and the demographic transition in developing countries: Theory and evidence - Nguyen Thang Dao; Julio Dávila; Angela Greulich (Osaka University, Institute of Social and Economic Research (ISER), 2019)
We propose a unified growth model linking technology, education investment across genders, and fertility to explain, for 20th century developing countries: (i) the demographic transition, (ii) the improvement in gender equality in education, and (iii) the transition to sustained growth. The mechanism comprises three components. First, technological progress reduces housework time - through the creation and diffusion of labor-saving home appliances - freeing women's time for childrearing and labor-force participation. Second, as housework time decreases, households invest relatively more in their daughters' education given its higher return - due to the initial imbalance - thus improving gender equality in education and increasing the opportunity cost of childrearing. Third, the narrowing of the education gender gap increases average human capital, accelerating technological progress. This reinforcing loop results in the transition to a new fertility regime and accelerated economic growth. We provide the empirical confirmation of the model's predictions using data from developing countries in the late 20th and early 21st centuries.
Keywords: J11; J13; J16; O11; O40; 330; Unified growth model; gender inequality; demographic transition; developing countries